2010
DOI: 10.1017/s1041610210001511
|View full text |Cite
|
Sign up to set email alerts
|

Depression literacy among older Chinese immigrants in Canada: a comparison with a population-based survey

Abstract: In light of these results, it is clear that older Chinese immigrants would benefit from information regarding the symptoms, etiology, and treatment of depression, and that this information may begin to address the serious underutilization of mental health services among this group. Our discussion highlights practice implications and promising interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…T tests were conducted to determine mean differences in the causal belief indices between the ‘mental illness label’ and the ‘indigenous label’ group. From prior studies, we expect that specific sociodemographic variables (gender, older age, fewer years of education, lower income; Tieu et al 2010; Wong et al in press), less acculturation to U.S. society (foreign birth, fewer years in the U.S., Chinese- speaking; Li et al 1999) and greater illness severity (greater number of hospitalizations and longer illness duration; Wong 2007) might be associated with whether relatives identify problems with a ‘mental illness’ label or not. We first identify whether these potential covariates are significantly associated with both the causal belief index and the mental illness label; any variables meeting this criterion are then controlled for.…”
Section: Methodsmentioning
confidence: 99%
“…T tests were conducted to determine mean differences in the causal belief indices between the ‘mental illness label’ and the ‘indigenous label’ group. From prior studies, we expect that specific sociodemographic variables (gender, older age, fewer years of education, lower income; Tieu et al 2010; Wong et al in press), less acculturation to U.S. society (foreign birth, fewer years in the U.S., Chinese- speaking; Li et al 1999) and greater illness severity (greater number of hospitalizations and longer illness duration; Wong 2007) might be associated with whether relatives identify problems with a ‘mental illness’ label or not. We first identify whether these potential covariates are significantly associated with both the causal belief index and the mental illness label; any variables meeting this criterion are then controlled for.…”
Section: Methodsmentioning
confidence: 99%
“…As expected, many of these studies were carried out in Australia by Jorm and his colleagues or other Australian researchers [15][16][17][18][19][20], and many others were conducted in other countries in different adult populations. For example, studies on mental health literacy among Chinese adults and elderly people had been conducted in China, Hong Kong, Australia, and Canada particularly in the area of depression and schizophrenia [18][19][20][21]. On the whole, the mental health literacy level among Chinese adults was not high [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies on mental health literacy among Chinese adults and elderly people had been conducted in China, Hong Kong, Australia, and Canada particularly in the area of depression and schizophrenia [18][19][20][21]. On the whole, the mental health literacy level among Chinese adults was not high [18][19][20][21]. For adolescents, studies on the MHL are far less in comparison to the adult population [22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, members of immigrant and ethnic minority groups generally fared worse in recognising mental health issues compared to members of the dominant ethnic/racial group. One study reported lower depression recognition rates for Chinese immigrants compared to their Canadian born counterparts . In another study older participants were more likely to identify depression if they were White, compared to Hispanics and African‐Americans .…”
Section: Resultsmentioning
confidence: 99%